Transient inclusion formation and evolution in silicon killed steels. (June 2015) - Thapliyal, V.; Kumar, A.; Robertson, D. G. C.; Smith, J. D.
<x content-type="archive" xml:space="preserve">Abstract</x> Transient inclusion formation in low carbon silicon killed steel as a result of ferroalloy additions of ferro-silicon (Fe75Si) and ferro-manganese (FeMn) (for de-oxidation and alloying) was studied in the laboratory using a novel experimental technique. Inclusion chemistries and morphologies were analysed using automated scanning electron microscopy (ASPEX). Formation of these inclusions was studied using thermodynamic software (FactSage) and a mechanism was proposed. Effect of solute concentration gradients during alloy dissolution and mixing was observed. Inclusions which formed initially, at low concentrations of ferroalloy, were liquid phase with a high concentration of FeO. Depending on the ferroalloy addition, initial inclusions become richer in SiO2 or MnO. Inclusions also underwent further phase transformations on cooling.